2020
DOI: 10.32677/ijch.2020.v07.i03.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of Bacillus clausii and Lactic acid bacillus in acute diarrhea

Abstract: dults and children commonly present with acute diarrhea due to various etiologies. Depending on the duration, acute diarrhea is defined as, the passage of three or more loose or liquid stools per day lasting for <14 days (<2 weeks) in duration [1]. It is of concern since acute diarrhea in children is one of the biggest public health problems related to higher morbidity and mortality rates. It is also the second leading cause of death in children under 5 years worldwide [1,2].To combat diarrheal diseases, many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Shah et al . (2020) showed that B . clausii (2 billion spores) along with ORS and zinc (bid) resumed normal stool consistency and frequency in infants and children suffering from acute diarrhoea.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shah et al . (2020) showed that B . clausii (2 billion spores) along with ORS and zinc (bid) resumed normal stool consistency and frequency in infants and children suffering from acute diarrhoea.…”
Section: Resultsmentioning
confidence: 99%
“…As example, De Castro et al (2020) reported a significant reduction in the duration of acute diarrhoea in children in the B. clausii group compared with the ORS with or without zinc supplementation from a meta-analysis of six randomised control trials involving 898 patients. Shah et al (2020) showed that B. clausii (2 billion spores) along with ORS and zinc (bid) resumed normal stool consistency and frequency in infants and children suffering from acute diarrhoea. Since, strains of A. clausii have therapeutic impact in various gastrointestinal and extraintestinal ailments, the use of various medicinal ingredients like cough syrup, gripe water, ORS, simethicone and others can potentially deliver A. clausii 088AE cells without compromising its viability at the site of action, i.e.…”
Section: Process and Storage Stability Of A Clausii 088aementioning
confidence: 99%
“…Shah et al. [ 41 ], in an interesting study (n = 225), determined the comparative therapeutic efficacy between B. clausii and L actic A cid B acillus (LAB) in children (<5 y). The study showed that a 4 billion CFU/day of B. clausii along with ORS + Zinc supplement showed better efficacy than LAB in terms of faster recovery and achieving normal stool frequency.…”
Section: Discussionmentioning
confidence: 99%